New Tools And Novel Approaches In Treating Locally Advanced Pancreatic Adenocarcinoma - Ahmed, Wesam B; Ng, John; Wazer, David E; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
Pancreatic adenocarcinoma is one of the most aggressive malignant tumors and represents the fourth leading cause of cancer-related death. The median survival of locally advanced pancreatic carcinoma is ten to thirteen months. In this year’s American Society of Clinical Oncology (ASCO) Annual Meeting, several studies were presented with novel approaches towards treating locally advanced pancreatic cancer. Wild et al. (Abstract #4055) explored a novel tool of selective delivery of TNF-alpha intratumoral injection. This approach limited the systemic toxicity, and suggested survival benefit in only the subgroup of patients with locally advanced pancreatic adenocarcinoma with stage T1-T3. Two studies were presented which were designed to assess the use of two novel agents, targeting signaling pathways, in addition to gemcitabine. Van Laethem et al. (Abstract #4050) are testing the MEK inhibitor, BAY 86-9766 in combination with gemcitabine. However, treatment related toxicity is still of concern. In the other study, Evans et al. (Abstract #TPS4134) are testing the combination of dasatinib and gemcitabine. This is a placebo-controlled, randomized, double blind phase II study. However, results are not available. Stereotactic body radiotherapy (SBRT) is an emerging technology with the comparative efficacy of single fraction radiotherapy (as is used in radiosurgery) vs. fractionated SBRT still unknown. Herman et al. (Abstract #4045) examined the role of fractionated SBRT in locally advanced pancreatic cancer. The phase II results showed a median overall survival of 15.9 months, suggesting that SBRT may be an emerging tool in the multi-modality treatment of locally advanced pancreatic cancer. Image: The principal teaching hospital for Tufts University School of Medicine. Boston, MA, USA.